Synthesis and Structural Verification of an ArI(OTf)2, NO2‐Ph‐I(OTf)2. (17th October 2022) - Sharp‐Bucknall, Lachlan; Tania,; Dutton, Jason L.
Abstract: PhI(OTf)2 and related ArI(OTf)2 species have been incorrectly invoked as intermediates in oxidation reactions for many years. We recently established that such compounds did not yet exist but remain an attractive target. Here we describe the synthesis, isolation, and structural characterization of NO2 ‐PhI(OTf)2, which is resistant to decomposition and more reactive than PhI(OTf)(OAc), the species previously misidentified as PhI(OTf)2 . Abstract : After many years of being invoked as an intermediate, the existence of PhI(OTf)2 was recently disproven. Taking advantage of a nitro substituent that suppresses decomposition; an NO2 ‐PhI(OTf)2 molecule has been synthesized and structurally characterized.